A proposal guide for social protection and limitation of sexual harassment against children. - Al-Shahri, Nawal bint Mohammed bin Saeed Al Jameeri (Journal of Humanities & Social Sciences, 2018)
The current study aimed to design a proposed guide for social protection to reduce sexual harassment against children. The Study adopted the qualitative approach by analyzing the content of the research interviews as a way to get to the answer for the questions of the study and achieve its objectives, the study purposeful sample of the study consisted of experts practitioner specialized in social service and social protection field. Sample number was (23) individually, the number of experts was (13), however the number of practitioner experts was (10), by applying the guide of semi-codified interview tool, The study concluded many results the most important of them are: 1- The study revealed the importance of provide a guide for social protection and limitation of sexual harassment against children, To organize and legalize the work of social workers those worked in different institutions concerned with children Away from randomness and personal interpretations